Tờ trình tóm tắt về Dự án Luật Quản lý, sử dụng vũ khí, vật liệu nổ và công cụ hỗ trợ (sửa đổi) - Chính phủ (2024)
Toàn văn Tờ trình tóm tắt về Dự án Luật Quản lý, sử dụng vũ khí, vật liệu nổ và công cụ hỗ trợ (sửa đổi).